Voluntary cleanups and redevelopment potential: Lessons from Baltimore, Maryland - Anna Alberini; Dennis Guignet (Fondazione Eni Enrico Mattei (FEEM), 2008)
Policy has increasingly shifted towards economic incentives and liability attenuation for promoting cleanup and redevelopment of contaminated sites, but little is known about the effectiveness of such policies. An example of such legislation is State Voluntary Cleanup Programs (VCPs), which were established in the US in the 1990s and to date have been implemented in almost every state. We examine Baltimore properties that participated in the Maryland VCP from its inception in 1997 to the end of 2006. Specifically, we examine what type of properties tend to participate in these programs, how these properties compare to other eligible but non-participating sites, and what is the redevelopment potential of VCP properties and implications towards open space conversion. We find that most applicants (66%) actually requested a No Further Action Determination directly, rather than proposing cleanup. VCP properties tend to be industrial, located in industrial areas, and away from residential neighborhoods. In more recent years larger industrial properties have increasingly enrolled in the program. The majority of sites are reused as industrial or commercial. In contrast to Alberini (2007), this suggests that pressure for residential development does not drive VCP participation. Based on differences in zoning requirements, the VCP may reduce demand for potentially contaminating activities on pristine land by as much as 1,238 to 6,444 acres, in Baltimore alone.
Keywords: R14; Q58; K32; 330; Brownfields; Contaminated Sites; Voluntary Cleanup Programs; Incentives